2009
DOI: 10.1074/jbc.m109.041905
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Long RNA Chains in Water

Abstract: The synthesis of RNA chains from 3,5-cAMP and 3,5-cGMP was observed. The RNA chains formed in water, at moderate temperatures (40 -90°C), in the absence of enzymes or inorganic catalysts. As determined by RNase analyses, the bonds formed were canonical 3,5-phosphodiester bonds. The polymerizations are based on two reactions not previously described: 1) oligomerization of 3, 5-cGMP to ϳ25-nucleotide-long RNA molecules, and of 3,5-cAMP to 4-to 8-nucleotide-long molecules. Oligonucleotide A molecules were further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
138
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(144 citation statements)
references
References 54 publications
5
138
1
Order By: Relevance
“…We observed [31] that 3 ,5 cyclic guanosine mono-phosphate (3 ,5 cGMP) and to some extent also 3 ,5 cAMP, afford short oligomers upon solubilization in water. Upon treatment in various conditions (see below), these oligomers undergo further polymerization.…”
Section: Abiotic Rnamentioning
confidence: 95%
See 4 more Smart Citations
“…We observed [31] that 3 ,5 cyclic guanosine mono-phosphate (3 ,5 cGMP) and to some extent also 3 ,5 cAMP, afford short oligomers upon solubilization in water. Upon treatment in various conditions (see below), these oligomers undergo further polymerization.…”
Section: Abiotic Rnamentioning
confidence: 95%
“…Passing to water chemistry, we describe previous studies and recent advancements on the oligomerization of cyclic purine nucleotides, both in the absence and in the presence of complementary template sequences, and on the nonenzymatic joining of oligomers to form long RNA chains [31]. Interestingly, we have recently observed that RNA polymerization may also occur in the presence of formamide (see Section 2.5).…”
Section: (Pre)genetics and (Pre)metabolismmentioning
confidence: 99%
See 3 more Smart Citations